Retraction notice to “Periodic Solutions of Second Order Impulsive Differential Equations at Resonance via Variational Approach” [Math. Model. Anal. 19(5):664–675, 2014] - Li, Jin; Luo, Jianlin; Wang, Zaihong (Mathematical Modelling and Analysis, 2015)
The following article is being retracted from publication in Mathematical Modelling and Analysis Journal: Periodic Solutions of Second Order Impulsive Diﬀerential Equations at Resonance via Variational Approach, by Jin Li, Jianlin Luo and Zaihong Wang, Volume 19, Issue 5, 2014, pp. 664–675, Mathematical Modelling and Analysis, DOI: 10.3846/13926292.2014.980864 http://www.tandfonline.com/doi/abs/10.3846/13926292.2014.980864 Received 10 February 2014, published online 24 November 2014, since the same results are published in Springer article Andesman-Lazer type condition for second-order diﬀerential equations at resonance with impulsive eﬀects, by Jin Li and Meilin Zheng, Advances in Diﬀerence Equations, DOI: 10.1186/1687-1847-2014-235 http://www.advancesindiﬀerenceequations.com/content/2014/1/235 Received 10 June 2014, published 9 September 2014.The Editors and publishers of the journal, Taylor & Francis, note that we received, peer-reviewed, accepted and published the article on the basis that the authors are presenting original results and are not intending to publish them in any other journal. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “retracted”.